2014
DOI: 10.5664/jcsm.3690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obstructive Sleep Apnea Hypopnea Syndrome on Lipid Profile: A Meta-Regression Analysis

Abstract: Background: Obstructive sleep apnea (OSA) is associated with obesity, metabolic syndrome, and dyslipidemia, which may be related to decrease androgen levels found in OSA patients. Dyslipidemia may contribute to atherosclerosis leading to increasing risk of heart disease. Methods: Systematic review was conducted using PubMed and Cochrane library by utilizing different combinations of key words; sleep apnea, obstructive sleep apnea, serum lipids, dyslipidemia, cholesterol, total cholesterol, low density lipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
87
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 48 publications
9
87
1
3
Order By: Relevance
“…45 AHI correlated positively with triglyceride levels and negatively with HDL levels but not with total cholesterol or LDL. 45 The association between OSA/AHI and triglyceride levels was also evident in non-obese patients 34 suggesting that relationship is independent of obesity and possibly more related to IR. However, despite these findings, a good evidence of causality between OSA and hyperlipidaemia is lacking, although mechanistically it is plausible that chronic intermittent hypoxia might lead to hyperlipidaemia via the generation of stearoylcoenzyme A desaturase-1 and oxidative stress, peroxidation of lipids and sympathetic activation.…”
Section: Obstructive Sleep Apnoea and Lipids In General Population Stmentioning
confidence: 98%
See 2 more Smart Citations
“…45 AHI correlated positively with triglyceride levels and negatively with HDL levels but not with total cholesterol or LDL. 45 The association between OSA/AHI and triglyceride levels was also evident in non-obese patients 34 suggesting that relationship is independent of obesity and possibly more related to IR. However, despite these findings, a good evidence of causality between OSA and hyperlipidaemia is lacking, although mechanistically it is plausible that chronic intermittent hypoxia might lead to hyperlipidaemia via the generation of stearoylcoenzyme A desaturase-1 and oxidative stress, peroxidation of lipids and sympathetic activation.…”
Section: Obstructive Sleep Apnoea and Lipids In General Population Stmentioning
confidence: 98%
“…The results are conflicting mainly due to differences in the population examined (particularly the choice of the control group, the sample size and the possible confounding effects of CPAP). 45,46 A recent meta-analysis of 64 studies showed that OSA was associated with higher total cholesterol, higher low-density lipoprotein (LDL), higher triglycerides and lower high-density lipoprotein (HDL). 45 AHI correlated positively with triglyceride levels and negatively with HDL levels but not with total cholesterol or LDL.…”
Section: Obstructive Sleep Apnoea and Lipids In General Population Stmentioning
confidence: 99%
See 1 more Smart Citation
“…57 However, cross-sectional studies were not consistent mainly due to differences in the population examined, study designs and the impact of CPAP. 57,58 A meta-analysis of 64 studies showed that OSA was associated with higher total cholesterol, higher low-density lipoprotein (LDL), higher triglycerides and lower high-density lipoprotein (HDL), while AHI correlated positively with triglycerides and negatively with HDL levels only. 58 The association between OSA/AHI and triglycerides is obesity independent.…”
Section: Osa Is Associated With Hyperlipidaemiamentioning
confidence: 99%
“…24 Further, a large 2015 cross-sectional study demonstrated an independent association between OSA and elevated LDL. 25 The association between OSA and dyslipidemia may mediate some of the excess cardiovascular morbidity and mortality risk associated with OSA.…”
mentioning
confidence: 99%